(untitled) (Palíndromo, 2013)
The videogames are a remarkable phenomenon in today’s culture. It highlights the importance of the game for humanity. The videogames are subject of interdisciplinary research and require dialogue between different professionals. By this way, the project "Dialogues between Art and Design" (UDESC / CNPq, 2012-2013) was proposed by six researchers of educational and/or artistic games. The dialogue is been guided by the game’s The Quelicera`s Mansion and a research that showed the qualities and improvement points about this game. This article presents the beginning of the "Dialogues between Art and Design" which has two goals: a) improve concepts and methods of development and evaluation of educational games, b) produce a new version of The Quelicera`s Mansion that will be free in web from 2013.